Unpacking the tracks: Diving into high-speed rail marketing research trends (2014–2024) and shaping the future of the field - Cep Abdul Baasith Wahpiyudin; Ujang Sumarwan; Megawati Simanjuntak; Irvan Nani (Asian Management and Business Review)
This study addresses the critical gap in understanding High-Speed Rail (HSR) marketing strategies in emerging Southeast Asian markets, such as Indonesia, where unique cultural, economic, and infrastructural factors require tailored approaches. Employing bibliometric analysis, the present study delves deeper into the evolution of HSR marketing from 2014 to 2023, analyzing 138 Scopus-indexed articles through R Studio (bibliometrix) and VOSviewer. The study identifies key trends, including the emphasis on pricing strategies, consumer behavior, and sustainability. An increase in publications, especially from emerging markets, indicates a growing interest in the marketing dynamics of HSR. Co-authorship networks and citation analysis highlight prominent authors and institutions, while keyword clustering reveals a shift toward customer satisfaction and environmental concerns. A significant gap in research emerges pertinent to HSR marketing strategies in Southeast Asia, pointing toward the need for region-specific approaches. The findings reveal a research gap in emerging markets like Indonesia, where themes such as “willingness to pay” and “tourism development” remain underexplored. As indicated by the low keyword density and thematic map results, future studies should focus more on consumer behavior and localized marketing strategies to support HSR adoption in diverse socio-economic contexts.